The Relationship between Nutrient Intake and Anemia with the Incidence of Deficiency Chronic Energy in Adolescent Women - Marliyana, Marliyana; Jana, Vilma Azizul; Suryadi, Suryadi; Fitri, Feni Elda; Yunitasari, Eva (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: Anemia is a health problem that is often experienced by adolescent girls, in Indonesia it reaches more than 30%. Anemia is characterized by low hemoglobin levels caused by insufficient intake of iron and other nutrients which, if prolonged for a long time, can lead to Chronic Energy Deficiency, and significantly affect the physical health, cognitive function, and overall quality of life of adolescent girls. This condition can lead to a variety of complications including learning disabilities, decreased physical fitness, and increased susceptibility to infections. Objective: to analyze the relationship between nutritional intake and anemia with the incidence of Chronic Energy Deficiency in adolescent girls. Methods: This study used a cross sectional design conducted in the dormitory of the Baitul Hikmah College of Health Sciences, a total of 92 subjects were purposively selected based on inclusion and exclusion criteria. The data was taken in February-March 2025.  Nutritional intake was obtained from food recall 2 × 24 hours and hemoglobin levels were measured using easy touch GCHb. Data were analyzed using the Chi-Square test. Results: The results of the study showed that as many as (18.7%) adolescent girls experienced anemia or hemoglobin (Hb) levels 12 g/dl and Chronic Energy Deficiency (27%). There was no association with nutrient intake (energy p=1.000), (protein p=0.674), (iron p=0.389), (vitamin A p=0.095) and there was a significant association of (vitamin C p=0.000) and (anemia p=0.000) with the incidence of Chronic Energy Deficiency in adolescent girls. Conclusion: the importance of prevention of anemia and Chronic Energy Deficiency by improving the quality of menus and nutritional intake in adolescent girls in dormitories.